FRI0291 Long term outcomes of children born to mothers with sle: predictors of child development and infections. (23rd January 2014) - Gayed, M.; Khamashta, M.; Culliford, D.; Leone, F.; Toescu, V.; Bruce, I.; Giles, I.; Teh, L.-S.; Mc Hugh, N.; Akil, M.; Edwards, C. J.; Gordon, C.
Abstract : Background: Certain immunosuppressive agents are used in pregnancy in SLE patients to prevent flare and ensure optimal outcome for mother and child. There is little literature regarding long term outcomes of children.US data suggested a link between azathioprine(AZA) and infection 1, and between anticardiolipin antibodies(abs) and developmental delay 2 have been suggested. Objectives: To assess if potential risk factors including maternal disease, autoantibodies, immunosuppression or other medication exposure influence health and behaviour of children. The following will be addressed:1)Does exposure to AZA in pregnancy &/or lactation increase risk of serious infections defined as requiring hospital assessment in the exposed children 2)Do immunosuppressive drugs or anti-phospholipid abs increase risk of developmental problems (delay±special needs±attention deficit disorder(ADD)±special educational needs). Methods: A cross sectional, retrospective study recruited women with 4 SLE ACR criteria attending 8 specialist UK clinics with pregnancy data for children under 17yrs born after maternal SLE diagnosis. A standard questionnaire developed for this multi-centre study and used in US was used to collect data. Potential factors influencing infection and developmental problems, assessed were AZA, prednisolone, hydroxychloroquine, aspirin or heparin use in pregnancy, antiphospholipid syndrome, lupus anticoagulant &/or anticardiolipin (IgG&/orIgM) abs. Potential confounders assessed were pregnancy duration, pre-eclampsia, intra-uterine growth restriction, low birth weight, child age at assessment, maternal age at delivery, disease duration, prior renal biopsy and smoking. Results: Complete data was available for 288 children born alive to 200 women: 66% Caucasian, 15% South Asian, 10% Afro-Caribbean, 1% Chinese, 1% Hispanic 4% other and 4% not stated. The median (range) age of women at delivery was 32 (19-44) yrs, and duration of maternal disease was 6 (0-27) yrs. Infections were reported in 45(16%) of children. The odds ratio (OR) for infection in children with exposure to AZA was 1.63 (95%CI 0.84-3.15, p=0.15). In total 14(4%) of children were reported to have developmental delays, 7(2.5%) special needs, 3(1%) ADD and 6(2%) special educational needs. OR for developmental problems with AZA exposure was 1.22, 95%CI 0.44-3.42, and if mothers had antiphospholipid abs was 0.73, 95%CI 0.22-2.35. The age of child at assessment was associated with a small increased risk of developmental problems OR 1.15, 95%CI 1.05-1.26, p=0.003. No other potential risk factors were associated with infections or developmental problems. Conclusions: No risk factors were identified for infection requiring hospital assessment, and only age of child at assessment was associated with increased risk of developmental problems. This study provides data to counsel women with SLE. References: Akhtaret al. Maternal Anticardiolipin Affects Childhood Development.A&R.2008.57:9, 443 Marderet al. In utero AZA exposure and increased utilization of special educational services in children born to mothers with SLE.A&R.2012:8:288 Acknowledgements: LupusUK Disclosure of Interest : None Declared